Bifunctional fluorescent probes for detection of amyloid aggregates and reactive oxygen species. Issue 2 (7th February 2018) - Needham, Lisa-Maria; Weber, Judith; Fyfe, James W. B.; Kabia, Omaru M.; Do, Dung T.; Klimont, Ewa; Zhang, Yu; Rodrigues, Margarida; Dobson, Christopher M.; Ghandi, Sonia; Bohndiek, Sarah E.; Snaddon, Thomas N.; et al.
Abstract : Protein aggregation into amyloid deposits and oxidative stress are key features of many neurodegenerative disorders including Parkinson's and Alzheimer's disease. We report here the creation of four highly sensitive bifunctional fluorescent probes, capable of H2 O2 and/or amyloid aggregate detection. These bifunctional sensors use a benzothiazole core for amyloid localization and boronic ester oxidation to specifically detect H2 O2 . We characterized the optical properties of these probes using both bulk fluorescence measurements and single-aggregate fluorescence imaging, and quantify changes in their fluorescence properties upon addition of amyloid aggregates of α-synuclein and pathophysiological H2 O2 concentrations. Our results indicate these new probes will be useful to detect and monitor neurodegenerative disease.